Macrophages in guided bone regeneration: potential roles and future directions - Gou, Min; Wang, Hang; Xie, Huiqi; Song, Hongjie (Frontiers in Immunology, 2024)
Guided bone regeneration (GBR) is one of the most widely used and thoroughly documented alveolar bone augmentation surgeries. However, implanting GBR membranes inevitably triggers an immune response, which can lead to inflammation and failure of bone augmentation. It has been shown that GBR membranes may significantly improve in vivo outcomes as potent immunomodulators, rather than solely serving as traditional barriers. Macrophages play crucial roles in immune responses and participate in the entire process of bone injury repair. The significant diversity and high plasticity of macrophages complicate our understanding of the immunomodulatory mechanisms underlying GBR. This review provides a comprehensive summary of recent findings on the potential role of macrophages in GBR for bone defects in situ. Specifically, macrophages can promote osteogenesis or fibrous tissue formation in bone defects and degradation or fibrous encapsulation of membranes. Moreover, GBR membranes can influence the recruitment and polarization of macrophages. Therefore, immunomodulating GBR membranes are primarily developed by improving macrophage recruitment and aggregation as well as regulating macrophage polarization. However, certain challenges remain to be addressed in the future. For example, developing more rational and sophisticated sequential delivery systems for macrophage activation reagents; addressing the interference of bone graft materials and dental implants; and understanding the correlations among membrane degradation, macrophage responses, and bone regeneration.